PERCEPTIONS OF USEFULNESS AND PERCEPTIONS OF EASINESS TO EMPLOYEES INTEREST IN USING FINTECH - Sri Mulyati; Bambang Sugiharto; Prini Nurtina Dewi (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
This study aims to examine the effect of perceived usefulness and perceived convenience on the interests of Lima Motor Subang employees in using fintech. The population used in this study were employees of Lima Motor Subang, with sample selection techniques using saturated sampling, and obtained 47 respondents. Data testing used in this research is multiple regression analysis, then to test the hypothesis using the F test, t test and the coefficient of determination (R2) with SPSS software version 22.0. The results of this study indicate that the variable of perceived usefulness and perceived convenience both partially and simultaneously affect the interest in using fintech.